Preparation method of high-conductivity organic silver paste for thermal printing head
Patent Information
- Application Number
- CN202611008756.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-09-01
AI Technical Summary
[0003]目前常规商用有机银浆存在诸多适配缺陷:其一,银粉单一粒径级配不合理,银粉堆积孔隙率高,浆料固化后导电通路残缺,导电电阻率偏高,无法满足热敏打印头高频通电导通需求;其二,配套玻璃粉热膨胀系数与AlN陶瓷基板不匹配,烧结后电极层易翘曲开裂、附着力差,长期通电发热易脱层断路;其三,有机载体耐热度不足,热敏打印头长期工作发热易造成电极老化、溶剂析出,电极绝缘性能下降;其四,浆料研磨工艺粗放,浆料粗细不均、内部气泡多,印刷流平性差,丝网印刷成型线路边缘毛刺多,良品率低;同时常规银浆疏水稳定性差,储存易银粉沉降团聚,批次导电性能波动大,使用寿命短,难以适配高精度长寿命热敏打印头量产使用
[0019] This method for preparing highly conductive organic silver paste for thermal printheads utilizes a three-level composite modified silver powder consisting of spherical, flake, and nano-sized particles. The powder is densely packed in multiple levels, creating a continuous, low-resistance conductive path. The finished silver paste exhibits high conductivity upon curing, with minimal heat loss during power-on, making it suitable for stable high-frequency operation of thermal printheads. The hydrophobic modification of the silver powder ensures no sedimentation or oxidation agglomeration during long-term storage, resulting in stable batch-to-batch performance of the paste.
Smart Images

Figure CN122677253A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of conductive paste material preparation and related products, specifically a method for preparing highly conductive organic silver paste for thermal printheads. Background Technology
[0002] Thermal printheads are core heating and conductive components in receipt printers, portable label printers, and cash registers. Their substrates are mostly AlN ceramic substrates, and conductive electrodes are formed by screen printing conductive silver paste and solidifying it to achieve heating resistance and main control pin conduction.
[0003] Currently, conventional commercial organic silver paste has several compatibility issues: First, the silver powder has an unreasonable single particle size distribution, resulting in high porosity and incomplete conductive pathways after curing, leading to high resistivity and inability to meet the high-frequency conductivity requirements of thermal printheads. Second, the thermal expansion coefficient of the matching glass powder is incompatible with the AlN ceramic substrate, causing the electrode layer to warp and crack after sintering, resulting in poor adhesion and potential delamination and circuit breakage due to long-term power-on heating. Third, the organic carrier has insufficient heat resistance, which can cause electrode aging, solvent precipitation, and decreased electrode insulation performance due to prolonged operation and heating of the thermal printhead. Fourth, the paste grinding process is crude, resulting in uneven paste size, numerous internal air bubbles, poor printing leveling, and many burrs on the edges of screen-printed lines, leading to a low yield rate. Furthermore, conventional silver paste has poor hydrophobic stability, making it prone to silver powder sedimentation and agglomeration during storage, resulting in large batch-to-batch conductivity fluctuations and short service life, making it difficult to adapt to mass production of high-precision, long-life thermal printheads. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing highly conductive organic silver paste for thermal printheads, so as to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a high-conductivity organic silver paste for thermal printheads, comprising the following raw materials by mass percentage: 78-84% modified composite silver powder, 2.5-4.5% low-temperature composite glass powder, 11-17% cross-linked organic carrier, and 0.6-1.2% functional additives;
[0006] The specific preparation steps are as follows:
[0007] S1. Pretreatment of graded hydrophobic modification of silver powder: Select three-grade compound silver powder, put it into a constant temperature modification kettle, add ethanol solution of modifier, stir and modify at constant temperature, filter and vacuum dry to obtain hydrophobic modified composite silver powder.
[0008] S2. Low-temperature composite glass powder melt modification: Weigh B2O3-SiO2-ZnO-Bi2O3 quaternary glass powder according to the formula, refine it by high-energy ball milling, heat up to melt, water quench and crush it, and air classify it through a 1200-mesh sieve to obtain ceramic-compatible modified glass powder.
[0009] S3. Preparation of heat-resistant crosslinking organic carrier: Mix the composite organic solvent, ethyl cellulose copolymer resin and crosslinking thickener, stir at 85-92℃ in a closed constant temperature until completely dissolved, degas under vacuum for 25-35 minutes, cool and let stand and filter to obtain a low-volatility heat-resistant crosslinking organic carrier.
[0010] S4. Segmented composite grinding and pulping: First, the modified composite silver powder, low-temperature composite glass powder, and half of the organic carrier are premixed at low speed to obtain a premixed slurry; then the remaining organic carrier and all functional additives are added, and the slurry fineness is controlled to be ≤7μm by gradient three-roll milling.
[0011] S5. Vacuum homogenization and maturation: The ground slurry is transferred to a vacuum homogenization tank, stirred and matured under negative pressure at room temperature, filtered to remove impurities, and a high-conductivity organic silver paste suitable for thermal printheads is obtained.
[0012] As a preferred embodiment of the present invention, the mass ratio of the three-stage compounded silver powder is as follows: 52-60% large-particle-size spherical silver powder, 30-38% medium-particle-size flake silver powder, and 8-12% nano-filled silver powder; the average particle size of the large-particle-size spherical silver powder is 2.2-3.0 μm, and the tap density is ≥4.2 g / cm³; the flake diameter of the medium-particle-size flake silver powder is 1.2-1.8 μm, and the flake thickness is 60-90 nm; the particle size of the nano-filled silver powder is 60-120 nm; the silver powder modifier is a compound of polyvinylpyrrolidone and stearic acid, with a compounding mass ratio of 2:1, the amount of modifier added is 1.2-1.8% of the total mass of silver powder, the modification temperature is 55-62℃, and the stirring time is 90-120 min.
[0013] As a preferred embodiment of the present invention, the mass ratio of the low-temperature composite glass powder components is: B2O3 52%, SiO2 14%, ZnO2 2%, Bi2O3 12%; the glass powder melting temperature is 680-720℃, the median particle size after ball milling is 1.0-1.6μm, and the coefficient of thermal expansion matches the AlN ceramic substrate, with a coefficient of thermal expansion of 4.1-4.5×10⁻. 6 / ℃.
[0014] As a preferred embodiment of the present invention, the crosslinked organic carrier is composed of the following components by mass: 76-82% composite organic solvent, 14-18% copolyethyl cellulose, and 2-6% polyamide crosslinking thixotropic agent; the composite organic solvent is a mixture of terpineol, butyl carbitol acetate, and isotridecyl alcohol ether in a mass ratio of 5:3:2.
[0015] As a preferred embodiment of the present invention, the functional additive is composed of dispersible modified lecithin, silane coupling agent KH-550, and antioxidant hindered phenol in a mass ratio of 4:3:2.
[0016] As a preferred embodiment of the present invention, the gradient three-roll milling process in step S4 is as follows: the first section has a roller gap of 25μm and is milled twice; the second section has a roller gap of 12μm and is milled three times; the third section has a roller gap of 6μm and is milled twice. The temperature is controlled at ≤38℃ throughout the milling process to avoid evaporation and aging of the slurry solvent.
[0017] As a preferred embodiment of the present invention, the vacuum homogenization and maturation parameters in step S5 are: vacuum degree -0.085--0.095MPa, stirring speed 45-60r / min, maturation time 45-60min, and finally, pressure filtration with a 200-mesh nylon filter to remove impurities.
[0018] Compared with the prior art, the beneficial effects of the present invention are:
[0019] This method for preparing highly conductive organic silver paste for thermal printheads utilizes a three-level composite modified silver powder consisting of spherical, flake, and nano-sized particles. The powder is densely packed in multiple levels, creating a continuous, low-resistance conductive path. The finished silver paste exhibits high conductivity upon curing, with minimal heat loss during power-on, making it suitable for stable high-frequency operation of thermal printheads. The hydrophobic modification of the silver powder ensures no sedimentation or oxidation agglomeration during long-term storage, resulting in stable batch-to-batch performance of the paste. Attached Figure Description
[0020] Figure 1 This is a schematic flowchart of a method for preparing highly conductive organic silver paste for thermal printheads according to the present invention. Detailed Implementation
[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0022] In the description of this invention, it should be noted that the terms "upper," "lower," "inner," "outer," "front end," "rear end," "both ends," "one end," and "the other end," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this invention and for simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0023] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installed," "equipped with," "connected," etc., should be interpreted broadly. For example, "connection" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can be a connection within two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.
[0024] Please see Figure 1 One embodiment of the present invention provides: a method for preparing a highly conductive organic silver paste for a thermal printhead.
[0025] Example 1
[0026] I. Raw material mass percentage ratio
[0027] The composition includes 78% modified composite silver powder, 4.5% low-temperature composite glass powder, 16.7% cross-linked organic carrier, and 0.8% functional additives.
[0028] II. Detailed Material Proportions
[0029] 1. Three-stage compound silver powder: 52% large-particle-size spherical silver powder, 38% medium-particle-size flake silver powder, and 10% nano-filled silver powder; physical properties: average particle size of spherical silver powder is 2.2μm, tap density is 4.3g / cm³; flake silver powder has a particle size of 1.5μm and a thickness of 75nm; nano silver powder has a particle size of 90nm. Silver powder modifier: polyvinylpyrrolidone:stearic acid = 2:1, the modifier is added at 1.2% of the total mass of silver powder.
[0030] 2. Low-temperature composite glass powder: B2O3 52%, SiO2 14%, ZnO 22%, Bi2O3 12%; melting temperature 690℃, median particle size after ball milling 1.2μm, coefficient of thermal expansion 4.2×10⁻ 6 / ℃, matching AlN ceramic substrate.
[0031] 3. Crosslinking organic carrier components: 79% composite organic solvent, 17% copolyethyl cellulose, 4% polyamide crosslinking thixotropic agent; composite organic solvent terpineol: butyl carbitol acetate: isomeric tridecanol ether = 5:3:2.
[0032] 4. Functional additives: Dispersed modified lecithin: silane coupling agent KH-550: antioxidant hindered phenol = 4:3:2 compound.
[0033] III. Stepwise Preparation Process Parameters
[0034] S1 silver powder modification: The modification temperature was 55℃, and the mixture was stirred at a constant temperature for 120 min. Ethanol solution was used as the dispersion medium. After modification, the mixture was vacuum dried and filtered to obtain hydrophobic modified composite silver powder.
[0035] S2 glass powder modification: Quaternary powder is ball-milled for 4 hours, heated to 700℃ for melting, quenched and crushed with pure water, and air-classified and passed through a 1200-mesh sieve for later use.
[0036] S3 organic carrier preparation: Dissolve the mixture by stirring at 90℃ in a sealed constant temperature, degas under vacuum for 30 minutes, cool and let stand, then filter through a 200-mesh filter for later use.
[0037] S4 segmented grinding: Take half of the cross-linked organic carrier + all the modified silver powder + all the glass powder and premix at low speed; add the remaining carrier + all functional additives; gradient three-roll milling: 25μm roller gap milling 2 times → 12μm roller gap milling 3 times → 6μm roller gap milling 2 times, temperature controlled at ≤35℃ throughout the process, and the final slurry fineness is 6.2μm.
[0038] S5 vacuum curing: vacuum degree -0.09MPa, stirring speed 50r / min, curing at room temperature for 50min, pressure filtration through a 200-mesh nylon filter to remove impurities, and obtain the finished silver paste.
[0039] Example 2
[0040] I. Raw material mass percentage ratio
[0041] The final formulation consists of 81% modified composite silver powder, 3.5% low-temperature composite glass powder, 14.2% cross-linked organic carrier, and 1.3% functional additives (correction: 1.2% functional additives, falling within the range of 0.6-1.2%).
[0042] II. Detailed Material Proportions 1. Three-stage compound silver powder: 56% large-particle-size spherical silver powder, 34% medium-particle-size flake silver powder, and 10% nano-filled silver powder; Properties: Spherical silver powder average particle size 2.6μm, tap density 4.5g / cm³; Flake silver powder flake diameter 1.5μm, flake thickness 70nm; Nano silver powder particle size 80nm. Silver powder modifier: Polyvinylpyrrolidone: Stearic acid = 2:1, modifier addition amount is 1.5% of the total silver powder mass.
[0043] 2. Low-temperature composite glass powder: fixed composition B2O3 52%, SiO2 14%, ZnO 22%, Bi2O3 12%; melting temperature 700℃, median particle size after ball milling 1.3μm, coefficient of thermal expansion 4.3×10⁻ 6 / ℃.
[0044] 3. Crosslinking organic carrier components: 78% composite organic solvent, 16% copolyethyl cellulose, and 6% polyamide crosslinking thixotropic agent; the solvent blending ratio remains unchanged at 5:3:2.
[0045] 4. Functional additives: Dispersed modified lecithin: KH-550: Antioxidant hindered phenol = 4:3:2 standard compound.
[0046] III. Stepwise Preparation Process Parameters
[0047] S1 silver powder modification: modification temperature 58℃, constant temperature stirring for 105 min, ethanol system modification, vacuum drying and filtration.
[0048] S2 glass powder modification: high-energy ball milling for 5 hours, molten water quenching at 705℃, and air classification sieving at 1200 mesh.
[0049] S3 organic carrier preparation: Dissolve by stirring in a closed container at 88℃, degas under vacuum for 32 minutes, cool and filter for later use.
[0050] S4 segmented grinding: equal amount of carrier premixed powder, followed by the addition of carrier and additives; gradient grinding process remains unchanged, temperature is controlled at ≤36℃ throughout the grinding process, and the fineness of the finished slurry is 5.1μm.
[0051] S5 Vacuum Curing: Vacuum degree -0.09MPa, stirring speed 55r / min, curing time 55min, pressure filtration with 200 mesh nylon filter.
[0052] Example 3
[0053] I. Raw material mass percentage ratio
[0054] The composition consists of 84% modified composite silver powder, 2.5% low-temperature composite glass powder, 12.9% cross-linked organic carrier, and 0.6% functional additives.
[0055] II. Detailed Material Proportions
[0056] 1. Three-stage compound silver powder: 60% large-particle-size spherical silver powder, 30% medium-particle-size flake silver powder, and 10% nano-filled silver powder; physical properties: average particle size of spherical silver powder is 3.0 μm, tap density is 4.8 g / cm³; flake silver powder has a particle size of 1.8 μm and a thickness of 85 nm; nano silver powder has a particle size of 110 nm. Silver powder modifier: polyvinylpyrrolidone: stearic acid = 2:1, the modifier is added at 1.8% of the total mass of silver powder.
[0057] 2. Low-temperature composite glass powder: fixed standard quaternary composition, melting temperature 715℃, median particle size after ball milling 1.5μm, coefficient of thermal expansion 4.5×10⁻ 6 / ℃, highly matching the sintering shrinkage rate of AlN ceramics.
[0058] 3. Crosslinking organic carrier components: 82% composite organic solvent, 14% copolyethyl cellulose, and 4% polyamide crosslinking thixotropic agent; the solvent blending ratio remains unchanged at 5:3:2.
[0059] 4. Functional additives: Standard 4:3:2 compound system.
[0060] III. Stepwise Preparation Process Parameters
[0061] S1 silver powder modification: modification temperature 62℃, constant temperature stirring for 90 min, ethanol modification system, vacuum drying to remove solvent.
[0062] S2 glass powder modification: high-energy ball milling for 6 hours, molten water quenching at 710℃, and air classification at 1200 mesh.
[0063] S3 organic carrier preparation: Dissolve by stirring at 92℃ under sealed constant temperature, degas under vacuum for 35 minutes, and then let stand to cool and filter.
[0064] S4 segmented grinding: First, half of the carrier is premixed into powder, then the remaining carrier and all additives are added; standard gradient three-roll milling, temperature controlled at ≤38℃ throughout the process, and the final slurry fineness is 4.5μm.
[0065] S5 vacuum curing: vacuum degree -0.095MPa, stirring speed 60r / min, curing time 60min, pressure filtration through a 200-mesh nylon filter to remove impurities, resulting in a highly conductive finished silver paste.
[0066] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
Claims
1. A method for preparing highly conductive organic silver paste for thermal printheads, characterized in that: It is prepared from the following raw materials by weight percentage: 78-84% modified composite silver powder, 2.5-4.5% low-temperature composite glass powder, 11-17% cross-linked organic carrier, and 0.6-1.2% functional additives; The specific preparation steps are as follows: S1. Pretreatment of graded hydrophobic modification of silver powder: Select three-grade compound silver powder, put it into a constant temperature modification kettle, add ethanol solution of modifier, stir and modify at constant temperature, filter and vacuum dry to obtain hydrophobic modified composite silver powder. S2. Low-temperature composite glass powder melt modification: Weigh B2O3-SiO2-ZnO-Bi2O3 quaternary glass powder according to the formula, refine it by high-energy ball milling, heat up to melt, water quench and crush it, and air classify it through a 1200-mesh sieve to obtain ceramic-compatible modified glass powder. S3. Preparation of heat-resistant crosslinking organic carrier: Mix the composite organic solvent, ethyl cellulose copolymer resin and crosslinking thickener, stir at 85-92℃ in a closed constant temperature until completely dissolved, degas under vacuum for 25-35 minutes, cool and let stand and filter to obtain a low-volatility heat-resistant crosslinking organic carrier. S4. Segmented composite grinding and pulping: First, the modified composite silver powder, low-temperature composite glass powder, and half of the organic carrier are premixed at low speed to obtain a premixed slurry; then the remaining organic carrier and all functional additives are added, and the slurry fineness is controlled to be ≤7μm by gradient three-roll milling. S5. Vacuum homogenization and maturation: The ground slurry is transferred to a vacuum homogenization tank, stirred and matured under negative pressure at room temperature, filtered to remove impurities, and a high-conductivity organic silver paste suitable for thermal printheads is obtained.
2. The method for preparing a highly conductive organic silver paste for a thermal printhead according to claim 1, characterized in that, The mass ratio of the three-stage compounded silver powder is as follows: 52-60% large-particle-size spherical silver powder, 30-38% medium-particle-size flake silver powder, and 8-12% nano-filled silver powder; the average particle size of the large-particle-size spherical silver powder is 2.2-3.0 μm, and the tap density is ≥4.2 g / cm³; the flake diameter of the medium-particle-size flake silver powder is 1.2-1.8 μm, and the flake thickness is 60-90 nm; the particle size of the nano-filled silver powder is 60-120 nm; the silver powder modifier is a compound of polyvinylpyrrolidone and stearic acid, with a compounding mass ratio of 2:1, and the amount of modifier added is 1.2-1.8% of the total mass of silver powder; the modification temperature is 55-62℃, and the stirring time is 90-120 min.
3. The method for preparing a highly conductive organic silver paste for a thermal printhead according to claim 1, characterized in that, The low-temperature composite glass powder composition is as follows: B2O3 52%, SiO2 14%, ZnO 22%, Bi2O3 12%; the glass powder melting temperature is 680-720℃, the median particle size after ball milling is 1.0-1.6μm, and the coefficient of thermal expansion matches the AlN ceramic substrate, with a coefficient of thermal expansion of 4.1-4.5×10⁻. 6 / ℃.
4. The method for preparing a highly conductive organic silver paste for a thermal printhead according to claim 1, characterized in that, The crosslinked organic carrier is composed of the following components by mass: 76-82% composite organic solvent, 14-18% copolyethyl cellulose, and 2-6% polyamide crosslinking thixotropic agent; the composite organic solvent is a mixture of terpineol, butyl carbitol acetate, and isotridecyl alcohol ether in a mass ratio of 5:3:
2.
5. The method for preparing a highly conductive organic silver paste for a thermal printhead according to claim 1, characterized in that, The functional additive is composed of dispersible modified lecithin, silane coupling agent KH-550, and antioxidant hindered phenol in a mass ratio of 4:3:
2.
6. The method for preparing a highly conductive organic silver paste for a thermal printhead according to claim 1, characterized in that, The step S4 gradient three-roll milling process is as follows: the first section has a roller gap of 25μm and is milled twice; the second section has a roller gap of 12μm and is milled three times; the third section has a roller gap of 6μm and is milled twice. The temperature is controlled at ≤38℃ throughout the milling process to avoid evaporation and aging of the slurry solvent.
7. The method for preparing a highly conductive organic silver paste for a thermal printhead according to claim 1, characterized in that, The parameters for vacuum homogenization and maturation in step S5 are: vacuum degree -0.085--0.095MPa, stirring speed 45-60r / min, maturation time 45-60min, and finally, pressure filtration using a 200-mesh nylon filter to remove impurities.